Penanaman Sikap Inspiratif Melalui Pendekatan Sains Teknologi Masyarakat - Sutaryono Sutaryono; Fitria Dwi Prasetyaningtyas (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2020)
The problems of this research are: 1) how to develop the approach of societal technology science?; 2) how is the feasibility approach of societal technology science; 3) is the approach of society technology science can cultivate the inspirational attitude?. This is a mixture between qualitatif and quantitative research. Qualitative research was chosen to describe the application of the society technology science. Quantitative research which is a pre-experimental design of one–group Pretest-Postest design, is to see the understanding and change of students’ character before and after the application of the model. The learning model development used the ADDIE (Analysis, Design, Develop, Implemen, Evaluation) design model. The results of this research are: 1) the development of society technology science approach to realize inspiring character was done through 5 stages. With the preliminary stages of approach, establishment/development concept, application in life, the improvement of concept, and assessment; 2) the approach of society technology science to create an inspiring attitude that has been developed, is declared feasible to be used with a score of 15 (90%) in ‘very decent’ criteria; 3) social technology science approach has reflected an inspiring attitude. This is shown from observations on the coursework and results of the student's work that earned an average yield of 3.6 on a ‘good’ category (90%). It is suggested planning a more mature, fuller and wider concept mastery component.